Effect of forms of nitrogen fertilizers on sheath blight of rice - PRASANTA K. SEN GUPTA, A. BASU and (Indian Phytopathology, 2002)
The effects of nitrogenous fertilizers on rice sheath blight caused by Rhizoctonia solani were studied in greenhouse experiments. Of the 3 N sources used, disease severity was lowest (27.4%) with calcium ammonium nitrate and highest (43.3%) with ammonium sulfate.